1987
DOI: 10.1080/00102208708947068
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous Oxide Concentrations in Coal,Oil,and Gas Furnace Flames

Abstract: Concentrations of NzO. NO" CO z• and O, were determined along the axis of coal, oil. and gas flames in a 3 MW experimental furnace, for both single-stage and two-stage combustion conditions. Concentrations of NO, and NzO were found to be strongly correlated along the flames and in the flue gas samples, with approximately one mole of N 20 produced for every three moles of NO,. The resulls suggested that most of the NO, and N 20 arose from oxidation of fuel nitrogen , with highest concentrations observed in coal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The majority of the world N 2 O emission is from agricultural soil management (74%) and secondly from stationary combustion (8%), particularly from the power plants [111]. N 2 O emission is a by-product of fuel combustion, arising from oxidation of fuel nitrogen [112]. Since coal contains a higher content of nitrogen, the highest concentrations of N 2 O are observed in coal flames and the lowest levels in the natural gas flame [113].…”
Section: Nitrous Oxide N 2 O Emissionmentioning
confidence: 99%
“…The majority of the world N 2 O emission is from agricultural soil management (74%) and secondly from stationary combustion (8%), particularly from the power plants [111]. N 2 O emission is a by-product of fuel combustion, arising from oxidation of fuel nitrogen [112]. Since coal contains a higher content of nitrogen, the highest concentrations of N 2 O are observed in coal flames and the lowest levels in the natural gas flame [113].…”
Section: Nitrous Oxide N 2 O Emissionmentioning
confidence: 99%
“…At the current rate of production, it is estimated that N O concentrations will reach roughly 375 ppb by the year 2030. This prospect has led many researchers (Pierotti and Rasmussen, 1976;Weiss and Craig, 1976;Elkine et al, 1978;Weiss, 1981;Keller et al, 1986;Hao et al, 1987;Roby and Bowman, 1987) to study N O emissions from natural and anthropogenic sources.…”
Section: Introductionmentioning
confidence: 97%
“…Various workers (Pierotti and Rasmussen, 1976;Weiss and Craig, 1976;Elkins et al, 1978;Weiss, 1981;Keller et al, 1986;Hao et al, 1987;Roby and Bowman, 1987;Hayhurst and Lawrence, 1992;Kramlich et al, 1982;Muzio et al, 1990;Smart et al, 1990;Kramlich et al, 1989;Martti et al, 1990;Bartok and Saro"m, 1991;Oude et al, 1992) have suggested the increasing trends of N O level in the atmosphere from the above-mentioned two sources and argued that combustion should represent an important anthropogenic input of N O to the atmosphere. The formation of N O from pulverized coal combustion has been studied by many researchers (Hayhurst and Lawrence, 1992;Kramlich et al, 1982;Muzio et al, 1990;Smart et al, 1990).…”
mentioning
confidence: 95%
“…22,23 Under the high temperature and pressure of internal-combustion engines, N 2 formation is preferred over N 2 O. 24 N 2 O is formed at relatively low catalyst temperatures, and it decomposes at higher temperatures. 5,25,26 In contrast, Toyoda et al (ref 6) concluded from a set of automobile experiments that the emission is largely affected by the running speed, mileage, and the catalytic converter temperature of vehicles.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The formation and release are complex and depend critically on the types of emission regulators installed . One important process to control the emission is the chemical reduction of NO x through a three-way catalyst. , It was found that N 2 O emission from catalyst-equipped gasoline light-duty vehicles is affected significantly by the type and the temperature of the catalyst and is insensitive to the total NO x levels or the fuel nitrogen content. , Under the high temperature and pressure of internal-combustion engines, N 2 formation is preferred over N 2 O . N 2 O is formed at relatively low catalyst temperatures, and it decomposes at higher temperatures. ,, In contrast, Toyoda et al (ref ) concluded from a set of automobile experiments that the emission is largely affected by the running speed, mileage, and the catalytic converter temperature of vehicles.…”
Section: Introductionmentioning
confidence: 99%